Perovskitas SrSnO3:Cu2+ impregnadas sobre suportes à base de SnO2-ZrO2 aplicadas na descoloração fotocatalítica de um azo corante - Silva, Suelen Alves de Lima (2016)
Perovskite stannates (ASnO3) are widely studied because they contain interesting features that provide its use as photocatalysts materials. In turn, oxides such as SnO2 and ZrO2 have used as catalysts or catalyst supports in the degradation of aqueous organic pollutants and photocatalytic processes. Generally, supported materials can be more efficient than bulk photocatalysts, due to better dispersion and generating new active sites. In this work, binary oxides (Sn1-xZrx)O2 and (Zr1-ySny)O2, where (0 ≤ x and y ≤ 10% mol) were prepared by solid state reaction. The perovskite SrSnO3:Cu2+ was prepared by modified Pechini method impregnated on supports synthesized in order to improve catalytic efficiency of the perovskite photodegradation of the Gold Yellow Remazol (RNL) dye. The photocatalysts were characterized by: X-ray Diffraction (XRD) at room temperature and hot-chamber, Infrared (IR), Raman and UV-visible (UV-VIS) spectroscopy, scanning electron microscopy (SEM) and specific surface area (BET). The XRD results showed that supports were monophasic and that impregnation process does not modified the structure of the perovskite. The IR and Raman spectra corroborate the XRD results, indicative of impregnating the perovskite surface of the supports observed by the presence of bands related to the SrCO3 arising from the perovskite, but also by the presence of active modes at 148, 180, 223, 253 cm-1 related to perovskite. The system SSO/ZS95 showed better photocatalytic activity, with an efficiency of 81% discoloration on the time of 4 hours, increasing by about 10 (ten) times the photocatalytic efficiency of SrSnO3, indicating that use of the catalytic support was effective, providing the dispersion of stannate (active phase).